The Insiders - Oshiro, Mark (Harper, an imprint of HarperCollinsPublishers, 2021)
Twelve-year-old Héctor Muñoz, fleeing from bullies, discovers a magical closet that not only provides him sanctuary, but also unites him with two other kids facing similar problems at their own schools, helping them find friendship and strength in each other.